Understanding poverty among the elderly in India: implications for social pension policy - Sarmistha Pal; Robert Palacios (Institute for the Study of Labor (IZA), 2008)
The Government of India is implementing a new policy which dramatically increases funding for a cash transfer program targeted to the poor elderly. The expansion of this 'social pension' in terms of coverage and benefit levels is taking place with little understanding of poverty among India's elderly or its determinants. This paper finds that households with elderly members do not have higher poverty rates than non-elderly households. This result is robust under various measures that take into account the size and composition of households. Separate evidence suggests that part of the explanation for this phenomenon is that the poor have higher mortality rates and are therefore underrepresented. This explanation has important implications for social pension policy and suggests that programs that reduce elderly mortality may actually increase the relative poverty levels of the elderly.
urn:nbn:de:101:1-2008040960
Keywords: J14; 330; Old age poverty; household demographic composition; adjusted poverty indices; elderly contribution; survivorship bias; Rentenpolitik; Armutspolitik; Alte Menschen; Armut; Sterblichkeit; Indien